Polyurethane resin composition and application thereof

By using a polyurethane resin composition in an organic optical resin, including curing composition, inorganic nanoparticles and additives, the problems of nanoparticle agglomeration and OLED display sensitivity to water, oxygen and heat are solved, and efficient optical properties and long-life packaging materials are achieved.

CN119708426APending Publication Date: 2025-03-28WUHAN SUNSHINE OPTOELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311251379.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

After adding inorganic nanoparticles with high refractive index, traditional organic optical resins are prone to nanoparticles agglomeration, resulting in poor light output efficiency. At the same time, OLED displays are sensitive to water, oxygen and heat, and external water vapor invasion increases the risk of device failure.

Method used

A polyurethane resin composition is used, including curing composition, inorganic nanoparticles and additives, and a crosslinking network of isocyanate functional groups and polyamine components is ensured to ensure good dispersion and storage stability of inorganic nanoparticles, and a highly crosslinked network structure is formed through a chemical moisture curing reaction.

Benefits of technology

It realizes good dispersion of inorganic nanoparticles, improves the light output efficiency and stability of optical materials, and at the same time, the bonding strength, wear resistance, high temperature resistance, water resistance and solvent resistance of the material are improved, and the service life of the OLED display device is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004470350400000091
    Figure BDA0004470350400000091
  • Figure FDA0004470350380000011
    Figure FDA0004470350380000011
  • Figure FDA0004470350380000012
    Figure FDA0004470350380000012
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to a polyurethane resin composition and application thereof. The polyurethane resin composition comprises the following components: a curing composition, inorganic nanoparticles and an auxiliary agent, the curing composition comprises a compound A, a compound B and a catalyst, the compound A contains 1-3 isocyanate functional groups, and the compound B is a low-molecular compound at least containing two reactive hydrogen; the ratio of the mole number of the isocyanate functional group to the mole number of the reactive hydrogen is (1-1.5): 1, and a dispersing aid is not contained. Based on the method, the polyurethane polymer with a highly-crosslinked net structure can be obtained, and the polyurethane polymer has the advantages of high bonding strength, low water vapor transmittance, high refractive index, high elongation at break and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a polyurethane resin composition and application thereof. Background Art

[0002] In modern materials science and technology, optical materials have become one of the most important components and have been widely used in many fields such as electronics, automobiles, building materials, coating devices, and information. Traditional optical materials mainly include two categories: inorganic optical materials and organic optical materials. Although inorganic optical materials have excellent characteristics such as high mechanical properties, high refractive index, and good optical transparency, traditional inorganic optical materials are gradually replaced by organic optical materials with excellent characteristics such as low density, easy processing, impact resistance, many types, and good optical properties due to their disadvantages such as difficulty in processing and molding, high density, and few types. Organic optical resins are widely used in the field of optical films, optical lenses, and different displays.

[0003] In order to save energy and improve the light extraction performance of optical devices, transparent inorganic nanoparticles with high refractive index, such as zinc oxide (ZnO), titanium dioxide (TiO2), zirconium dioxide (ZrO2), etc., are usually added to organic optical resins to improve the light extraction efficiency of the resin. However, inorganic nanoparticles are prone to agglomeration in acrylic resins. Even if the particle surface energy can be reduced by reducing the particle size and surface modification of the particles, thereby reducing particle agglomeration, the percentage of inorganic particles that can be grafted with active groups after surface modification is usually small, and when the content of inorganic particles is too high, agglomeration will still occur, which cannot meet the requirements for improving light extraction efficiency. In addition, OLED displays are extremely sensitive to water, oxygen, and heat, and the intrusion of external water vapor will increase the risk of failure of OLED devices. Optical materials with excellent water and oxygen barrier capabilities, as well as high refractive index and good light transmittance are imperative. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a polyurethane resin composition, comprising the following components: a curing composition, inorganic nanoparticles and an additive; the curing composition includes a compound A, a compound B and a curing catalyst, the compound A contains 1 to 3 isocyanate functional groups, the compound B is a compound containing at least 2 active hydrogen functional groups that can react with the isocyanate functional groups, and the molar number of the isocyanate functional groups is greater than the molar number of the active hydrogen.

[0005] Furthermore, the added amounts of the curing composition, inorganic nanoparticles and auxiliary agent are 40-61 parts of the curing composition, 20-60 parts of the inorganic nanoparticles and 1-5 parts of the auxiliary agent, respectively, in parts by weight.

[0006] Furthermore, the polyurethane resin composition does not contain a dispersing aid.

[0007] Preferably, the compound A has the structural formula shown in Formula 1: Wherein L1 and L2 are independently selected from hydrogen, substituted or unsubstituted C1-C 15 Alkyl, C1-C 15 The cycloalkyl group or aryl group is selected from the group consisting of: L1 and L2, and L1 and L2 are not hydrogen atoms at the same time.

[0008] Preferably, the compound A is selected from one or more combinations of cyclohexane diisocyanate, toluene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, ethyl(yl)phenyl(yl) diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, methylene diphenyl diisocyanate, naphthalene diisocyanate, anthracene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, 1,8-diisocyanooctane, hexamethylene diisocyanate, and lysine diisocyanate.

[0009] Preferably, the low molecular weight compound containing an amine group has the structural formula shown below: m is an integer of 1-3, R1 is C 10 -C 20 An alkyl group having a C3-C8 cycloalkyl group, an aliphatic group having 1 to 3 C3-C6 cycloalkyl groups, or an aryl group having 1 to 2 benzene rings.

[0010] Preferably, the C1-C 20 The alkyl group is selected from propane, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, n-pentyl, 2-pentyl, 3-pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl, nonane, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl and octadecyl; the aliphatic alkane containing 1-3 C3-C6 cycloalkyl groups is selected from bicyclobutane, dicyclopentane, bicyclohexane or decalin; the aryl group containing 1-2 benzene rings is selected from phenyl, naphthyl, anthracenyl, biphenyl, diphenylmethane or diphenylethyl.

[0011] Furthermore, the low molecular weight compound containing an amine group is selected from decylamine, undecylamine, dodecylamine, tetradecylamine, hexadecylamine, propylenediamine, decyldiamine, dodecyldiamine, 1,4-butylenediamine, 1,3-phenylenediamine, 3-aminomethylcyclohexylmethylamine, 4,4-methylenebiscyclohexylamine, 3,3'-dimethyl-4,4-diaminodicyclohexylmethane, laurylpropylenediamine, cyclohexyldiamine, 1,2-cyclooctanediamine, 1,2-cycloheptyldiamine, isophoronediamine, propylenetriamine, and triaminebenzene.

[0012] Furthermore, the weight ratio of the compound A to the compound B is (1-4):1.

[0013] Preferably, the curing catalyst is selected from one or more combinations of organic amine catalysts and organic metal catalysts; the organic amine catalyst is selected from at least one of triethylamine, triethylenediamine, N,N-dimethylcyclohexylamine, N,N-diethylpiperazine, triethanolamine, N,N-dimethylpyridine, and dimorpholine diethyl ether; the organic metal is selected from at least one of zinc isooctanoate, bismuth isooctanoate, dibutyltin dilaurate, stannous octoate, di(dodecylsulfide) dibutyltin, stannous oleate, stannous chloride, tetra-n-butyltin, hydroxytrimethyltin, and dibutyltin dilaurate. The curing catalyst is used to catalyze the curing of compound A and compound B.

[0014] Preferably, the auxiliary agent includes one or more combinations of antioxidants, tackifying resins, and chain extenders.

[0015] Furthermore, the antioxidant is selected from at least one of antioxidant 264, antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, and 2,6-di-tert-butyl-4-methylphenol, and the added amount is 0.1 to 1 part by weight.

[0016] Furthermore, the tackifying resin is selected from at least one of rosin, terpene resin, alkylphenolic resin, xylene resin and rosin glycerol ester, and the added amount is 0.1 to 1 parts by weight.

[0017] The chain extender is selected from at least one of ethylene glycol, propylene glycol, hexylene glycol, neopentyl glycol, cyclohexanediol, methyl propanediol, trimethylol propane, glycerol, pentaerythritol, xylitol and sorbitol, and the added amount is 1 to 3 parts by weight. The chain extender can be the same as the low molecular weight compound containing an amine group.

[0018] Preferably, the inorganic nanoparticles are selected from any one or more combinations of Si3N4, NiO, Al2O3, ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, and Nd2O3. The inorganic nanoparticles have a particle size range of 15-20 nm.

[0019] On the other hand, the present invention provides an application of a polyurethane resin composition for preparing an encapsulation material layer in an OLED, MiniLED, or Micro LED display device.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In the prior art, a prepared polyurethane resin is generally used, which has a high viscosity and needs to be added with a diluent to reduce the viscosity in order to redisperse the inorganic nanoparticles;

[0022] In the present invention, inorganic nanoparticles are added to the raw materials for preparing polyurethane resins. The viscosity of isocyanate and polyamine monomers is low, and the inorganic nanoparticles can be well dispersed in the raw materials and then well dispersed in the resin. Therefore, no additional diluent is needed. In addition, the inorganic nanoparticles are restricted in the cross-linked network of isocyanate and polyamine monomers, and their microscopic movement is restricted, which has excellent storage stability.

[0023] The resin of the polyurethane resin composition after curing has excess isocyanate reactive groups after the curing reaction, which can then undergo a chemical wet curing reaction with water molecules in the air or compounds containing active hydrogen, and finally form a highly cross-linked network structure polyurethane polymer with high bonding strength, wear resistance, high temperature resistance, water resistance, solvent resistance and other excellent properties. And through the regulation of the content of isocyanate functional groups and polyamine components, the optical material obtained after the composition is formed into a film still has highly hygroscopic groups isocyanate, so that the infiltrated water molecules can be captured, further improving the service life of the display device. DETAILED DESCRIPTION

[0024] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0025] In the embodiment, the inorganic nanoparticles are added in the form of being mixed with a commercially available dispersant: the dispersing solvent is commercially available PGMEA (propylene glycol methyl ether acetate), and the wt% of the inorganic nanoparticles is 40-60%. In this embodiment, the mass fraction of the inorganic nanoparticles is 50%.

[0026] Preparation Example:

[0027] A1: Add the weighed compound B and the auxiliary agent into a three-necked flask, turn on the heating device and the stirrer, control the reaction temperature at 80°C, evacuate the flask to an absolute pressure of 70Pa, continue heating to 120°C, and maintain this temperature and pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, and cool it down to 80°C;

[0028] A2: Under nitrogen protection, weighed compound A and catalyst were added into the reactor in sequence, the nitrogen control switch was turned off, the vacuum pump and the stirrer were turned on, the absolute pressure in the flask was controlled to 80Pa, the temperature of the reactants in the flask was controlled to 80°C, and the reaction was maintained under this condition for about 2h;

[0029] A3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85°C, and react for 2 hours to obtain a polyurethane resin composition.

[0030] Embodiment 1:

[0031] 32 parts by weight of cyclohexane diisocyanate, 16 parts by weight of cyclohexylamine, 25 parts by weight of TiO2, 0.1 parts by weight of bismuth isooctanoate, 0.1 parts by weight of antioxidant 1010, 0.1 parts by weight of terpene resin, and 1 part by weight of hexanediol.

[0032] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0033] Embodiment 2:

[0034] 40 parts by weight of cyclohexane diisocyanate, 20 parts by weight of 3-aminomethylcyclohexylamine, 60 parts by weight of TiO2, 1 part by weight of dibutyltin dilaurate, 1 part by weight of antioxidant 164, 1 part by weight of rosin glycerol ester, and 3 parts by weight of hexanediol.

[0035] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0036] Embodiment 3:

[0037] 30 parts by weight of p-phenylene diisocyanate, 20 parts by weight of decylamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0038] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0039] Embodiment 4:

[0040] 35 parts by weight of hexamethylene diisocyanate, 25 parts by weight of 1,3-phenylenediamine, 40 parts by weight of TiO2, 0.5 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of cyclohexanediol.

[0041] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0042] Embodiment 5:

[0043] 30 parts by weight of p-phenylene diisocyanate, 20 parts by weight of dodecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyl tin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0044] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0045] Embodiment 6:

[0046] 30 parts by weight of p-phenylene diisocyanate, 20 parts by weight of tetradecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0047] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0048] Embodiment 7:

[0049] 30 parts by weight of p-phenylene diisocyanate, 20 parts by weight of hexadecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1076, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0050] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0051] Embodiment 8:

[0052] 30 parts by weight of naphthalene diisocyanate, 20 parts by weight of dodecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0053] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0054] Embodiment 9:

[0055] 40 parts by weight of toluene diisocyanate, 10 parts by weight of propylenetriamine, 30 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0056] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0057] Comparative Example 1:

[0058] 35 parts by weight of hexamethylene diisocyanate, 25 parts by weight of 1,3-phenylenediamine, 40 parts by weight of TiO2, 0.5 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, 2 parts by weight of cyclohexanediol, and 50 parts by weight of propylene glycol methyl ether acetate as a diluent.

[0059] Preparation of polyurethane optical materials:

[0060] S1: Add weighed 1,3-phenylenediamine, antioxidant 1010, terpene resin, and cyclohexanediol into a three-necked flask according to the proportion, turn on the heating device and the stirrer, control the reaction temperature at 80°C, evacuate the flask to an absolute pressure of 70Pa, continue heating to 120°C, and maintain this temperature and pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, and cool it down to 80°C;

[0061] S2: under nitrogen protection, weighed hexamethylene diisocyanate and dibutyltin dilaurate amine were added into the reactor in sequence, the nitrogen control switch was turned off, the vacuum pump and the stirrer were turned on, the absolute pressure in the flask was controlled to 80Pa, the temperature of the reactants in the flask was controlled to 80°C, and the reaction was maintained under this condition for 2h;

[0062] S3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85℃, and react for 2h to obtain the polyurethane resin.

[0063] S4: Add the polyurethane resin, propylene glycol methyl ether acetate and TiO2 obtained in step S3 into a three-necked flask, turn on the heating device and the stirrer, and stir evenly.

[0064] Since the polyurethane resin has a relatively high viscosity (>2000cps), it cannot be directly used for optical materials. Therefore, a solvent component (propylene glycol methyl ether acetate) is added in this comparative example.

[0065] Comparative Example 2:

[0066] 30 parts by weight of p-phenylene diisocyanate, 20 parts by weight of dodecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyl tin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, 2 parts by weight of hexanediol, and 50 parts by weight of propylene glycol methyl ether acetate.

[0067] Preparation of polyurethane optical materials:

[0068] S1: Add weighed dodecanediamine, antioxidant 1010, terpene resin and hexylene glycol into a three-necked flask according to the proportion, turn on the heating device and stirrer, control the reaction temperature at 80-85°C, evacuate the flask to an absolute pressure of 70Pa, continue heating to 120°C, and maintain this temperature and pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, and cool it down to 80°C;

[0069] S2: Under nitrogen protection, weighed p-phenylene diisocyanate and dibutyltin dilaurate amine were added to the reactor in sequence, the nitrogen control switch was turned off, the vacuum pump and the stirrer were turned on, the absolute pressure in the flask was controlled to 80Pa, the temperature of the reactants in the flask was controlled to 80°C, and the reaction was maintained under this condition for 2h;

[0070] S3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85℃, and react for 2h to obtain the polyurethane resin.

[0071] S4: Add the polyurethane resin, propylene glycol methyl ether acetate and ZrO2 obtained in step S3 into a three-necked flask, turn on the heating device and the stirrer, and stir evenly.

[0072] Since the polyurethane resin has a relatively high viscosity (>2000cps), it cannot be directly used for optical materials. Therefore, a solvent component (propylene glycol methyl ether acetate) is added in this comparative example.

[0073] Comparative Example 3:

[0074] 20 parts by weight of p-phenylene diisocyanate, 30 parts by weight of tetradecane diamine, 40 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.5 parts by weight of antioxidant 1010, 0.5 parts by weight of terpene resin, and 2 parts by weight of hexanediol.

[0075] The polyurethane resin composition was prepared according to the method of Preparation Example.

[0076] Performance testing:

[0077] The resin compositions prepared in Examples 1-9 and Comparative Examples 1-3 were numbered 1-12, respectively. The polyurethane resin compositions numbered 1-12 were preheated at 100° C. for 20 min, and then placed in a constant temperature and humidity environment at 298K (25° C.) and a relative humidity of 80% for 2 h. The isocyanate groups were fully reacted and cross-linked using moisture (H2O) to prepare test specimens. The AGS-X universal testing machine was used to test the isocyanate groups at 2000 mJ / cm 2The elongation at break was measured; the water vapor transmission rate was tested at 30°C and 85% RH using a moisture permeability tester based on the moisture permeability cup weighing method; the curing hardness of the optical material was measured using a hardness tester. The test results are shown in Table 1 below:

[0078] Table 1

[0079]

[0080] As can be seen from the above table, the encapsulation composition is prepared by mixing an isocyanate monomer component with a polyamine, and has a viscosity between 10-13 cps, which is convenient for use and mixing with inorganic nanoparticles, thereby reducing the agglomeration of the inorganic nanoparticles and improving the refractive index of the encapsulation composition; the water vapor permeability of Examples 1-9 is lower than that of Comparative Examples 1-3 (Comparative Examples 1 and 2 respectively add inorganic nanoparticles after obtaining the resin, and Comparative Example 3 reduces the amount of isocyanate monomer). This may be due to the entry of water vapor and the reaction with the isocyanate group, which further increases the cross-linking degree of the optical adhesive, thereby improving the compactness of the encapsulation material, and then improving the mechanical properties and stability of the encapsulation material. Therefore, while achieving a water-blocking effect, the service life of the encapsulation material is effectively improved.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A polyurethane resin composition, characterized in that: The invention comprises the following components: a curing composition, inorganic nanoparticles and an auxiliary agent; the curing composition comprises a compound A, a compound B and a curing catalyst, the compound A contains 1 to 3 isocyanate functional groups, the compound B is a compound containing at least 2 active hydrogen functional groups that can react with the isocyanate functional groups, and the molar number of the isocyanate functional groups is greater than the molar number of the active hydrogen.

2. The polyurethane resin composition according to claim 1, characterized in that: The compound A has the structural formula shown in Formula 1: Wherein L1 and L2 are independently selected from hydrogen, substituted or unsubstituted C1-C 15 Alkyl, C3-C 15 A cycloalkyl group containing 1 to 3 benzene rings or 1 to 3 condensed benzene rings; L1 and L2 are not hydrogen atoms at the same time.

3. The polyurethane resin composition according to claim 2, characterized in that The compound A is selected from one or more combinations of cyclohexane diisocyanate, toluene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, ethyl(phenyl)diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, methylene diphenyl diisocyanate, naphthalene diisocyanate, biphenyl diisocyanate, anthracene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, 1,8-diisocyanooctane, hexamethylene diisocyanate, and lysine diisocyanate.

4. The polyurethane resin composition according to claim 2, characterized in that: The compound B is a low molecular weight compound containing an amine group, and has the following structural formula: m is an integer of 1 to 3, and R1 is C1 to C 20 The invention can be any one or more of an alkyl group, a C3-C8 cycloalkyl group, an aliphatic alkyl group containing 1 to 3 C3-C6 cycloalkyl groups, or an aryl group containing 1 to 2 benzene rings.

5. The polyurethane resin composition according to claim 4, characterized in that: C1~C 20 The alkyl group is selected from the group consisting of propane, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, n-pentyl, 2-pentyl, 3-pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl, nonane, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl or octadecyl; The aliphatic alkane containing 1-3 C3-C6 cycloalkyl groups is selected from bicyclobutane, dicyclopentane, bicyclohexane or decalin; The aryl group containing 1-2 benzene rings is selected from phenyl, naphthyl, anthracenyl, biphenyl, diphenylmethane or diphenylethyl.

6. The polyurethane resin composition according to claim 4, characterized in that: The weight ratio of the compound A to the compound B is (1-4):

1.

7. The polyurethane resin composition according to claim 1, characterized in that: The curing catalyst is selected from one or more combinations of organic amine catalysts and organic metal catalysts; the organic amine catalyst is selected from at least one of triethylamine, triethylenediamine, N,N-dimethylcyclohexylamine, N,N-diethylpiperazine, triethanolamine, N,N-dimethylpyridine, and dimorpholine diethyl ether; the organic metal catalyst is selected from at least one of zinc isooctanoate, bismuth isooctanoate, dibutyltin dilaurate, stannous octoate, dibutyltin (dodecylsulfide), stannous oleate, stannous chloride, tetra-n-butyltin, hydroxytrimethyltin, and dibutyltin dilaurate.

8. The polyurethane resin composition according to claim 1, characterized in that: The auxiliary agent includes one or more of an antioxidant, a tackifying resin or a chain extender; the antioxidant is selected from at least one of antioxidant 264, antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164 or 2,6-di-tert-butyl-4-methylphenol; the tackifying resin is selected from at least one of rosin, terpene resin, alkylphenolic resin, xylene resin or rosin glycerol ester; the chain extender is the same as the low molecular weight compound containing an amine group.

9. The polyurethane resin composition according to any one of claims 1 to 8, characterized in that: The inorganic nanoparticles are selected from any one or more combinations of Si3N4, NiO, Al2O3, ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5 or Nd2O3.

10. An application of the polyurethane resin composition according to any one of claims 1 to 9, characterized in that: Used to prepare optical material layers in OLED, Mini LED or Micro LED display devices.